Examining the spatial consistency of palaeosol proxies: Implications for palaeoclimatic and palaeoenvironmental reconstructions in terrestrial sedimentary basins. Issue 4 (17th January 2016) - Hyland, Ethan G.; Sheldon, Nathan D.
Abstract: Terrestrial sediments are a significant archive of past conditions, and the 'critical zone' in particular is important for understanding past and ongoing interactions between the atmosphere, biosphere and lithosphere. Understanding the details of a palaeolandscape or palaeocatena record can greatly improve palaeoenvironmental descriptions and palaeoclimate reconstructions during crucial time periods in the past. This article presents multi‐proxy data including palaeosol descriptions, major element geochemistry, magnetic composition and stable isotope geochemistry from an early Eocene palaeosol transect, which show distinct trends in palaeosol features and geochemistry across the landscape, particularly in terms of the differences between A‐horizon and B‐horizon samples. A‐horizon geochemical and physical features are highly variable and reflect other not strictly pedogenic controls, whereas B‐horizon composition is extremely consistent. Given that most palaeoclimatic or palaeoenvironmental proxies based on palaeosols use B‐horizon features, these results highlight the robustness of those proxies. At the same time, the difference between A‐horizons and B‐horizons and the variability within A‐horizons of the same palaeosol in different geomorphic settings underscores the importance of palaeosol description, detailed sampling, and a multi‐proxy approach to produce both precise and accurate reconstructions of past environments and climates using terrestrial sedimentary records.